# Determining the infinite sum $\sum\limits_{n=0}^{\infty}\frac{(-1)^n}{2n+1}$

I have to determine the following sum:

$$\begin{equation} \sum\limits_{n=0}^{\infty}\frac{(-1)^n}{2n+1} \end{equation}$$

And i've tried lot's of ways to determine it, but i couldn't get a result so I figured I would look on WolframAlpha to see what the result has to be so i could maybe know what to do next by that. But apparently the result is $$\frac{\pi}{4}$$ and i don't know how I could possibly get to pi. Does anyone have any suggestions about how to tackle this?

Observe $$\frac{1}{1-x}=\sum_{n=0}^\infty x^n$$

$$\frac{1}{1+x^2}=\sum_{n=0}^\infty (-1)^nx^{2n}$$

Integrating both sides from $$0$$ to $$1$$ we get $$\arctan(x)|_0^1=\sum_{n=0}^\infty \frac{(-1)^n x^{2n+1}}{2n+1}|_0^1$$ so $$\arctan(1)=\frac{\pi}{4}=\sum_{n=0}^\infty \frac{(-1)^n}{2n+1}$$

• Thanks i now understand why this is the case! – Viktor Jan 7 at 18:30

Hint: $$\sum_{k=0}^n{\frac{(-1)^k}{2k+1}} = \int_0^1{\frac{1}{1+x^2}} - \int_0^1{\frac{(-x^2)^{n+1}}{1+x^2}}$$.

$$\frac{d(\tan^{-1}(x))}{dx}=\frac{1}{1+x^2}$$ This is because, let $$y=\tan^{-1}(x)$$, so that $$x=\tan(y)\tag{1}$$ Differentiating both sides of $$(1)$$ yields $$1=\frac{1}{\cos^2(y)}\frac{dy}{dx}\\ 1=\frac{\cos^2(y)+\sin^2(y)}{\cos^2(y)}\frac{dy}{dx}\\\\1=\left(1+x^2\right)\frac{dy}{dx}$$ $$\boxed{\frac{d(\tan^{-1}(x))}{dx}=\frac{1}{1+x^2}}\tag{2}$$

Now, it is known that $$\frac{1}{1-x}=\sum_{n=0}^{\infty}x^n$$ for $$|x|<1$$, replacing $$x$$ with $$-x^2$$ we get $$\frac{1}{1+x^2}=\sum_{n=0}^{\infty}(-1)^nx^{2n}\tag{3}$$ Combining $$(2)$$ and $$(3)$$ we see that $$\frac{d(\tan^{-1}(x))}{dx}=\sum_{n=0}^{\infty}(-1)^nx^{2n}\tag{4}$$ Taking the integral from $$0$$ to $$1$$ of $$(4)$$ yields $$\int_0^1\frac{d(\tan^{-1}(x))}{dx}=\tan^{-1}(1)-\tan^{-1}(0)=\sum_{n=0}^{\infty}\frac{(-1)^n}{2n+1}\\\boxed{\frac{\pi}{4}=\sum_{n=0}^{\infty}\frac{(-1)^n}{2n+1}}$$

As others have shown, $$\sum_{n\geq0}\frac{(-1)^n}{2n+1}=\int_0^1\frac{\mathrm dx}{1+x^2}$$ but we can generalize this.

$$\frac1{1+x}=\sum_{n\geq0}(-1)^nx^n$$ $$\frac1{1+x^a}=\sum_{n\geq0}(-1)^nx^{an}$$ $$\int_0^1\frac{\mathrm dx}{1+x^a}=\sum_{n\geq0}\frac{(-1)^n}{an+1}$$ Also $$\int_0^b\frac{\mathrm dx}{1+x^a}=\sum_{n\geq0}\frac{(-1)^nb^{an+1}}{an+1}$$